Analisis Pengaruh Perubahan PPN 12% Terhadap Kepatuhan Wajib Pajak Di Indonesia - Alisya Hariani; Winny Lian Seventeen (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This research aims to analyze the effect of changing the Value Added Tax (VAT) rate to 12% on the level of taxpayer compliance in Indonesia. Using a quantitative approach, this research analyzes secondary data in the form of company financial reports and tax compliance data obtained from the Directorate General of Taxes. The research results show that the increase in VAT rates significantly increases state revenues, but does not automatically increase the level of taxpayer compliance. Several other factors such as the effectiveness of supervision, tax awareness, and ease of tax administration also influence the level of compliance. This research concludes that the government needs to make various efforts to increase taxpayer compliance, including by strengthening the supervision system, providing more intensive tax education, and simplifying tax procedures. This research explores the indirect impact of a 12% VAT rate increase on taxpayer compliance in Indonesia, with a focus on Micro, Small and Medium Enterprises (MSMEs). Through case studies and in-depth interviews, this research found that the increase in VAT rates put significant financial pressure on MSMEs, so that some of them chose not to report taxes or reported them incompletely. Apart from that, this research also analyzes taxpayers' perceptions regarding tax fairness and the effectiveness of tax services. The research results show that a more progressive fiscal policy and greater support for MSMEs is needed to increase tax compliance